Ten-Year after the Asian Financial Crisis: Understanding Spread Determinants on New Emerging Market Bonds - Ugut, Gracia S. (UI Scholars Hub, 2009)
The spread determinants of emerging market bonds have shown some similarity with the non-investment grade bonds. In the study, the author found that there are significant numbers of quantitiable factors to explain the variance in the risk premium. The factors were classified into company speciic variables and macroeconomic variables, such as rating, term, and secondary market spread, interest rate change and rising price of commodities. For the unexplained variance in risk premiums, the study suggested some explanation on the underwriter's effectiveness in presenting the issuer to the investors and correlation of the emerging-market debt to the other asset classes.